Impacts of central government supervision on rural local governance and development: case study of Zaka rural district council - Mutangamhazha, Amon (2017)
The research topic is based on the impacts of central government supervision on rural local governance and development using Zaka rural district council as the case study. Central government supervision has proved that it can run in two ways either producing positive or negative impacts in as much as rural local governance and development is concerned. Zaka rural district council has not been spared when incompetent rural local authorities are being counted. The district has been characterized by poor performance, salary backlogs for employees, incapability in the delivery of services, poor road networks, poor living standards, slow rate of rural urban development. All these deteriorating standards have played a center stage whilst central government claims to be responsible for regulation, monitoring and intervention in local authorities. The central question in place is whether these forms of supervision are bringing effectiveness and efficiency in the day to day operations of Zaka RDC and in its effort to fight against the deteriorating service delivery standards. The researcher used both qualitative and quantitative research methods in trying to collect data relating to the forms of central government supervision instruments being used to monitor the activities of Zaka RDC and the impacts born by these instruments on rural local governance and development. Data was collected using both purposive and simple random sampling to collect data from the population which included the District administrator, government ministries, local authority management, employees and councilors. The findings were presented using graphs, tables and charts in a bid to clearly illustrate on the findings. Key findings showed that central government supervision have got both positive and negative impacts on rural local governance and development but the negative impacts are many than the positive ones. Conclusions were presented and a list of possible recommendations on the impacts of central government supervision was outlined.